A flame retardant PP / SEBS foam composite material and preparation method thereof

By using polyphosphate and triazine carbonizer CFA as flame retardant in PP/SEBS foam composite materials, and combined with siane coupling agent modified nano -nanosilica as a nuclear agent, optimized materials formula, solved it to solve the solution The flammable problem of PP/SEBS foam composite materials has achieved good flame retardant performance and foam performance.

CN119144086BActive Publication Date: 2025-01-28ANHUI LASUN COMMUNICATION CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411657655.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-28
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

Due to its flammability, PP/SEBS foamed composite materials will release a large amount of heat energy and melt droplets during combustion, which poses huge safety hazards and is difficult to have excellent flame retardant and foaming properties.

Method used

The CFA of polyphosphate and triazine -like carbon -tech agent is used as a flame retardant, combined with the modified nano -sanxin silicon dioxide as a nuclear agent to optimize the formula of PP/SebS foam composite materials to form APP/CFA flame retardant The system and melamine modified nano -sanxide are reproduced.

Benefits of technology

Under the premise that PP/SEBS foam composite materials are significantly improved, the foaming performance has been significantly improved, and the materials that have excellent flame retardant performance and foam performance are obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144086B_ABST
    Figure CN119144086B_ABST
Patent Text Reader

Abstract

The invention discloses a flame retardant PP / SEBS foam composite material and a preparation method thereof, and relates to the technical field of foam materials. The foam composite material of the invention comprises the following raw materials in parts by weight: 100 parts of polymer material, 3-5 parts of foaming agent AC, 1-3 parts of modified or unmodified nano silicon dioxide, and 20-25 parts of flame retardant; the polymer material is composed of PP and SEBS, wherein PP accounts for 80-95% of the total mass of the polymer material, and SEBS accounts for 5-20% of the total mass of the polymer material; the flame retardant is composed of ammonium polyphosphate and triazine carbon forming agent CFA in a mass ratio of 2-3:1. The PP / SEBS foam composite material of the invention has excellent flame retardant properties, mechanical properties and foaming properties, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of foaming materials, and in particular to a flame-retardant PP / SEBS foaming composite material and a preparation method thereof. Background Art

[0002] Polypropylene (PP) foam material has the characteristics of good heat resistance, strong chemical resistance, low cost, easy to obtain, non-toxic and recyclable, and is widely used in automobile, construction, industry, packaging and other industries. However, as a linear crystalline polymer material, PP has low melt strength in the molten state and cannot support the pores inside the melt. The pores break and deform during the growth process, and the foaming quality is poor. This leads to the difficulty of controlling the production process of PP foam material, and also leads to poor appearance quality, which is not conducive to subsequent processing and other problems. In order to avoid poor foaming caused by melt strength, it is usually possible to add other high melt strength polymer components for blending, and improve the foaming effect by improving the melt strength. SEBS is an elastomeric material obtained by hydrogenation of styrene-butadiene-styrene (SBS). It has stable chemical properties, excellent aging resistance, good processing performance, etc. It can effectively increase the melt strength of PP. PP / SEBS foam composite materials have the characteristics of high foaming quality, light weight, excellent appearance quality, and easy processing. It is a foam composite material with broad application prospects. However, both PP and SEBS as the base materials are flammable. When burning, PP / SEBS foam composite materials can release a large amount of heat energy and produce molten droplets, which can easily spread the flame and cause the fire to spread, posing a huge safety hazard. Therefore, it is necessary to develop a PP / SEBS foam composite material with both excellent flame retardant properties and foaming properties. Summary of the invention

[0003] Based on the technical problems existing in the background technology, the present invention proposes a flame retardant PP / SEBS foamed composite material and a preparation method thereof.

[0004] The invention provides a flame-retardant PP / SEBS foamed composite material, which comprises the following raw materials in parts by weight: 100 parts of polymer material, 3-5 parts of foaming agent AC, 1-3 parts of modified or unmodified nano silicon dioxide, and 20-25 parts of flame retardant; the polymer material consists of PP and SEBS, wherein PP accounts for 80-95% of the total weight of the polymer material, and SEBS accounts for 5-20% of the total weight of the polymer material; the flame retardant consists of ammonium polyphosphate and triazine carbonizing agent CFA in a mass ratio of 2-3:1.

[0005] Preferably, the modified nano-silica is nano-silica modified by a silane coupling agent.

[0006] Preferably, the silane coupling agent is at least one of silane coupling agent KH-550, silane coupling agent KH-560 and silane coupling agent KH-570.

[0007] In the present invention, there is no particular limitation on the preparation method of silane coupling agent modified nano-silica, and it can be prepared by conventional preparation methods in the art. For example, it can be:

[0008] Nano-silicon dioxide is added to ethanol and dispersed evenly, and then a silane coupling agent is added dropwise, and the mixture is heated and stirred for reaction. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain the product; preferably, the temperature of the heating and stirring reaction is 50-80° C., and the time is 2-5 hours.

[0009] Preferably, the mass ratio of the silane coupling agent to nano-silicon dioxide is 0.1-0.5:1.

[0010] Preferably, the modified nano-silica is melamine-modified nano-silica;

[0011] The preparation method of the melamine-modified nano-silica comprises the following steps:

[0012] (1) adding nano-silica to a solvent and fully dispersing the nano-silica to obtain a nano-silica dispersion; adding a silane coupling agent KH-550 and succinic anhydride to the solvent, stirring and reacting to obtain a modified solution; adding the silicon dioxide dispersion to the modified solution, stirring and reacting, and then centrifuging, washing, and drying to obtain carboxylated nano-silica;

[0013] (2) In a protective atmosphere, the carboxylated nano-silica, melamine and a condensing agent are added to a solvent and mixed thoroughly, and then heated and stirred for reaction, centrifuged, washed and dried to obtain melamine-modified nano-silica.

[0014] Preferably, in step (1), the solvent is DMF (N,N-dimethylformamide).

[0015] Preferably, in step (1), the mass ratio of the nano-silica to the silane coupling agent KH-550 and succinic anhydride is 1:0.2~0.4:0.1~0.2.

[0016] Preferably, in step (1), silane coupling agent KH-550 and succinic anhydride are added to a solvent, and the mixture is stirred and reacted at room temperature for 1 to 5 hours to obtain a modified solution.

[0017] Preferably, in step (1), the silicon dioxide dispersion is added to the modified solution, stirred for reaction at room temperature for 3 to 6 hours, and then centrifuged, washed, and dried to obtain carboxylated nano-silica.

[0018] Preferably, in step (2), the mass ratio of the carboxylated nano-silica to melamine and the condensing agent is 1:0.1-0.2:0.05-0.15;

[0019] Preferably, in step (2), the condensation agent is dicyclohexylcarbodiimide (DCC).

[0020] Preferably, in step (2), the solvent is pyridine.

[0021] Preferably, in step (2), the temperature of the heating and stirring reaction is 60-95° C., and the time is 24-48 hours.

[0022] In the present invention, the protective atmosphere refers to an atmosphere formed by a protective gas, and the protective gas may be, for example, nitrogen, argon, or helium.

[0023] Preferably, the particle size of the nano-silicon dioxide is 50-100 nm.

[0024] The present invention also proposes a method for preparing the flame-retardant PP / SEBS foamed composite material, comprising the following steps:

[0025] S1, adding raw materials into an internal mixer for stirring and blending to obtain a mixture;

[0026] S2. After the mixture is pressed into a green body, it is placed in a mold, and then the mold is placed in a hot press at a temperature of 190-220° C., first preheated, then pressurized to 8-15 MPa, maintained at pressure for 3-8 minutes, cooled to room temperature, and released to obtain.

[0027] Preferably, in S1, the stirring and blending temperature is 160-200°C, the rotation speed is 30-80 r / min, and the time is 15-30 min.

[0028] Preferably, in S2, the preheating time is 2 to 5 minutes.

[0029] The beneficial effects of the present invention are as follows:

[0030] The present invention optimizes the formula of the PP / SEBS foamed composite material, selects a suitable PP / SEBS ratio, a suitable foaming agent, a nucleating agent and a flame retardant system, and obtains a PP / SEBS foamed composite material that has excellent flame retardant properties and good pore structure and mechanical properties, and can meet the requirements of safety performance and use performance.

[0031] In particular, the present invention can achieve a synergistic effect by compounding an APP / CFA flame retardant system with a melamine-modified nano-silica nucleating agent in an appropriate ratio, so that the foaming performance of the PP / SEBS foamed composite material is significantly improved while having excellent flame retardant performance, thereby obtaining a PP / SEBS foamed composite material with both excellent flame retardant performance and foaming performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a cross-sectional SEM image of the foamed composite material PP / SEBS-6 prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is described in detail below through specific embodiments.

[0034] In the following examples and comparative examples:

[0035] Polypropylene (PP) was purchased from Sinopec Thailand Branch with the brand number 1100NK;

[0036] SEBS was purchased from Wuhan Meistone Biochemical Technology Co., Ltd., brand SEBS 6150;

[0037] Nano-silica was purchased from Shanghai MacLean Biochemical Co., Ltd. with a particle size of 50-100 nm;

[0038] The foaming agent AC (azodicarbonamide) was purchased from Shanghai MacLean Biochemical Co., Ltd.;

[0039] Ammonium polyphosphate (APP) was purchased from Aladdin;

[0040] Expandable graphite (EG) was purchased from Qingdao Yanhai Carbon Materials Co., Ltd. with an average size of 1000 mesh;

[0041] The triazine carbon-forming agent CFA was purchased from Guangzhou Yinyuan New Materials Co., Ltd. with the brand name FR-CFA. Example

[0042] Prepare the raw materials of the foam composite material according to the mass ratio in Table 1:

[0043] Table 1

[0044]

[0045] In Table 1, the polymer material consists of PP and SEBS in a mass ratio of PP:SEBS=85:15.

[0046] The foamed composite material was prepared according to the raw material formula in Table 1. The preparation method is as follows:

[0047] S1. Add the raw materials into an internal mixer, stir and blend for 20 minutes at a temperature of 180° C. and a rotation speed of 50 r / min to obtain a mixture;

[0048] S2. After the mixture is pressed into a green body, it is placed in a mold, and then the mold is placed in a hot press at a temperature of 210° C., preheated for 3 minutes, and then pressurized to 10 MPa. After maintaining the pressure for 5 minutes, it is cooled to room temperature and released to obtain.

[0049] The mechanical properties and flame retardant properties of the foamed composite material prepared above were tested, and the test method was as follows:

[0050] Tensile properties test: An electronic universal testing machine was used to test in accordance with GB / T1040.2-2006. The test specimens were dumbbell-shaped specimens with a size of 75 mm × 5 mm × 2 mm. The test was carried out at room temperature at a tensile rate of 20 mm / min. At least 5 specimens were taken for each group of samples for testing, and the test results were averaged.

[0051] Bending performance test: An electronic universal testing machine was used to test according to the standard of GB / T1449-2005. The test specimen was a long strip with a size of 80 mm × 10 mm × 4 mm. The span was set to 60 mm during the test. The test was carried out at a bending rate of 2 mm / min at room temperature. At least 5 specimens were taken for each group of samples for testing, and the test results were averaged.

[0052] Impact performance test: XJJD-5.5 electronic cantilever impact testing machine was used for testing according to GB / T1843-2008 standard. The test specimen was a long strip with a size of 80 mm × 10 mm × 4 mm. The energy of the pendulum was 7.5 J. At least 5 specimens were taken for each group of samples at room temperature for testing, and the test results were averaged.

[0053] Limiting oxygen index test (LOI): Use an oxygen index tester to measure the limiting oxygen index (LOI) of the foamed specimen according to GB / T2406.2-2009. The test specimen size is 80 mm×10 mm×4 mm. The oxygen and nitrogen flows are controlled by two glass rotor flowmeters to adjust the oxygen concentration in the combustion tube. The top of the sample is ignited, and the oxygen concentration in the oxygen-nitrogen mixed flow gradually decreases until the combustion of the sample stops. The oxygen concentration value recorded at this time is the limiting oxygen index (LOI).

[0054] Vertical combustion test (UL-94): The vertical combustion performance test is used to test the flame combustion behavior in the vertical direction. The test specimen is 130 mm × 13 mm × 1.6 mm. Fix one end of the specimen to the fixture, set the flame device nozzle 10 mm away from the lower end of the specimen, use an ignition device with a power of 50W, and adjust the flame height to 20 mm. Start the experiment, push the ignition device into the bottom of the specimen and immerse it in the flame for a length of 10 mm for the first flame impact, the duration is 10s, quickly pull the ignition device away from the specimen, and record the time when the specimen flame goes out as t1. Push the ignition device into the bottom of the specimen again for the second flame impact, the duration is also 10s, and record the time when the flame goes out as t2. Record the time from the flame going out to the complete disappearance of the afterglow in the specimen as t3. According to the test results, the flame retardant effect is divided into three levels from high to low: V-0, V-1 and V-2. The specific standards are shown in Table 2.

[0055] Table 2

[0056]

[0057] In Table 2, t1 is the afterflame extinguishing time of the sample after the first flame impact; t2 is the afterflame extinguishing time of the sample after the second flame impact; t3 is the afterglow time after the sample is extinguished. The experimental equipment is a vertical combustion instrument, the specific experimental steps are in accordance with the GB / T2408-2021 implementation standard, and at least 5 samples are tested in each group.

[0058] The above test results are shown in Table 3:

[0059] Table 3

[0060]

[0061] As can be seen from Table 3, the flame retardant properties of the PP / SEBS foam composite material without adding flame retardant are very poor; and although the flame retardant properties of the PP / SEBS foam composite material with the addition of APP / EG flame retardant system are improved, the improvement effect on the flame retardant properties is still not ideal, and its vertical combustion grade is V-1 at most, which does not meet the requirements for flame retardant properties. At the same time, since EG is an inorganic flame retardant, it is unevenly dispersed in the polymer matrix, resulting in a significant decrease in mechanical properties; while using APP / CFA as the flame retardant system, APP and CFA show a good synergistic flame retardant effect, and can reach a vertical combustion grade of V-0 at a suitable ratio, with excellent flame retardant properties, and the effect of the APP / CFA flame retardant system on the mechanical properties is relatively small, because both APP and CFA are organic substances and can be better dispersed in the polymer matrix.

[0062] The prepared foam composite material PP / SEBS-6 was subjected to SEM testing. The testing method was as follows: the prepared foamed specimen was immersed in liquid nitrogen for at least 30 minutes and then quenched and broken. The cell structure of the cross section was observed by scanning electron microscopy. The cross section SEM image of the above material is shown in FIG. Figure 1 As shown. Figure 1 It can be seen that the pore structure of the material is uniform and has good foaming quality.

[0063] Taking the raw material formula of the foam composite material PP / SEBS-6 prepared above as the benchmark, only the nano-silica is replaced by nano-silica modified by silane coupling agent KH-550, and the obtained foam composite material is recorded as PP / SEBS-10; only the nano-silica is replaced by melamine-modified nano-silica, and the obtained foam composite material is recorded as PP / SEBS-11. The specific formulas (mass parts) of PP / SEBS-10 and PP / SEBS-11 are shown in Table 4:

[0064] Table 4

[0065]

[0066] In Table 4:

[0067] The polymer material is composed of PP and SEBS in a mass ratio of PP:SEBS=85:15;

[0068] The preparation method of silane coupling agent KH-550 modified nano-silica is as follows: 1g of nano-silica is added to 100mL of ethanol for ultrasonic dispersion, and then 0.2g of silane coupling agent KH-550 is added dropwise, and the mixture is heated and stirred at 60°C for reaction for 4h. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain the product.

[0069] The preparation method of melamine-modified nano-silica is as follows:

[0070] (1) Add 1 g of nano-silica into 50 mL of DMF and fully disperse to obtain a nano-silica dispersion; add 0.2 g of silane coupling agent KH-550 and 0.1 g of succinic anhydride into 50 mL of DMF, stir and react at room temperature for 3 hours to obtain a modified solution; add the silica dispersion prepared above into the modified solution prepared above, stir and react at room temperature for 5 hours, then centrifuge, wash, and dry to obtain carboxylated nano-silica;

[0071] (2) In a nitrogen atmosphere, 1 g of carboxylated nano-silica, 0.15 g of melamine, and 0.1 g of dicyclohexylcarbodiimide were added to 100 mL of pyridine and mixed thoroughly. The mixture was then heated and stirred at 90 °C for 30 h. The mixture was centrifuged, washed, and dried to obtain melamine-modified nano-silica.

[0072] The mechanical properties, flame retardancy and pore structure tests were performed on the foamed composite material prepared above, wherein the pore structure test method is as follows:

[0073] The prepared foamed specimens with the specifications of 80 mm×10 mm×4 mm were completely immersed in liquid nitrogen and cooled for 30 min. After the specimens were taken out, they were quickly quenched. The cross-section of the PP / SEBS foamed material was observed and tested for the microscopic pore structure using a scanning electron microscope (Zeiss Ultra Plus, Zeiss, Germany). The electron acceleration voltage during scanning was 5 kV. The average pore diameter D0 of the sample can be calculated according to the following formula:

[0074]

[0075] Where D0 refers to the average cell diameter (μm), d i It refers to the diameter of each cell, and n is the number of cells.

[0076] Cell density (N0) is the number of cells per unit volume of the foaming material, and the formula is as follows:

[0077]

[0078] Where n is the number of cells in the statistical area, A is the image area of ​​the statistical area (cm 2 ). Φ is the volume expansion ratio of the foaming material, and the calculation formula of Φ is as follows:

[0079]

[0080] Where ρs is the resin density and ρf is the density of the foaming material.

[0081] The mechanical properties, flame retardancy and pore structure test results of the foamed composite material prepared above are shown in Table 5:

[0082] Table 5

[0083]

[0084] As shown in Table 5, the PP / SEBS-6 foamed composite material has excellent flame retardant properties, good cell structure and mechanical properties; however, compared with the PP / SEBS-0 foamed composite material without adding flame retardant, its mechanical properties and foaming effect still have a significant decline. In order to further improve the mechanical properties and foaming effect of the material, the present invention further modifies the nucleating agent nano-silica, and replaces the nucleating agent with silane coupling agent KH-550 modified nano-silica and melamine modified nano-silica, and compares the performance of the prepared PP / SEBS-10 foamed composite material and PP / SEBS-11 foamed composite material. It can be seen that the use of nano-silica modified with silane coupling agent KH-550 as a nucleating agent has certain improvements on the mechanical properties and foaming effect. This is because the modification of the silane coupling agent makes the nano-silica nucleating agent more evenly distributed in the polymer matrix, which can better play a nucleating role, thereby improving the mechanical properties and foaming effect. However, the improvement is not large, especially for the foaming effect, the reduction of the pore diameter and the increase of the pore density are not obvious; while the use of melamine-modified nano-silica as a nucleating agent has more obvious improvements on the mechanical properties and foaming effect, especially the increase of the pore diameter. The diameter of the foamed composite material is significantly reduced and the pore density is significantly increased, indicating that the foaming effect of the foamed composite material is significantly improved under the premise of ensuring excellent flame retardant properties. This is because, on the one hand, the melamine grafted on the surface of nano-silica can improve its dispersion uniformity in the polymer matrix, thereby better playing a nucleating role. On the other hand, there is a strong interaction between the triazine groups in the melamine on the surface of the nucleating agent and the triazine groups in CFA. When it serves as a foaming nucleation site, it can bring stronger resistance to the merging and collapse of the pores, thereby helping to reduce the pore diameter, increase the pore density, and improve the foaming effect.

[0085] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A flame retardant PP / SEBS foam composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of polymer material, 3-5 parts of foaming agent AC, 1-3 parts of melamine-modified nano-silicon dioxide, and 20-25 parts of flame retardant; the polymer material is composed of PP and SEBS, wherein PP accounts for 80-95% of the total weight of the polymer material, and SEBS accounts for 5-20% of the total weight of the polymer material; the flame retardant is composed of ammonium polyphosphate and triazine carbonizing agent CFA in a weight ratio of 2-3:1; The preparation method of the melamine-modified nano-silica comprises the following steps: (1) adding nano-silica to a solvent and fully dispersing the nano-silica to obtain a nano-silica dispersion; adding a silane coupling agent KH-550 and succinic anhydride to the solvent, stirring and reacting to obtain a modified solution; adding the silicon dioxide dispersion to the modified solution, stirring and reacting, and then centrifuging, washing, and drying to obtain carboxylated nano-silica; (2) In a protective atmosphere, the carboxylated nano-silica, melamine and a condensing agent are added to a solvent and mixed thoroughly, and then heated and stirred for reaction, centrifuged, washed and dried to obtain melamine-modified nano-silica.

2. The flame-retardant PP / SEBS foamed composite material according to claim 1, characterized in that: In step (1), the mass ratio of the nano-silica to the silane coupling agent KH-550 and succinic anhydride is 1:0.2-0.4:0.1-0.2; In step (1), the solvent is DMF.

3. The flame-retardant PP / SEBS foamed composite material according to claim 1, characterized in that: In step (2), the mass ratio of the carboxylated nano-silica to melamine and the condensing agent is 1:0.1-0.2:0.05-0.15; In step (2), the condensation agent is dicyclohexylcarbodiimide; In step (2), the solvent is pyridine.

4. A method for preparing the flame-retardant PP / SEBS foamed composite material according to any one of claims 1 to 3, characterized in that: The steps include: S1, adding raw materials into an internal mixer for stirring and blending to obtain a mixture; S2. After the mixture is pressed into a green body, it is placed in a mold, and then the mold is placed in a hot press at a temperature of 190-220° C., first preheated, then pressurized to 8-15 MPa, maintained at pressure for 3-8 minutes, cooled to room temperature, and released to obtain.

5. The method for preparing the flame-retardant PP / SEBS foamed composite material according to claim 4, characterized in that: In S1, the stirring and blending temperature is 160-200°C, the rotation speed is 30-80 r / min, and the time is 15-30 min.

6. The method for preparing the flame-retardant PP / SEBS foamed composite material according to claim 4, characterized in that: In S2, the preheating time is 2 to 5 minutes.

Citation Information

Patent Citations

  • Hybridized melamine-formaldehyde silicon aerogel modified flame-retardant polypropylene foaming plate and preparation method thereof

    CN106750940A

  • High-flame-retardant foaming modified styrene thermoplastic elastomer and preparation method thereof

    CN116041894A